Transcriptome and Metabolome Analyses of Codonopsis convolvulacea Kurz Tuber, Stem, and Leaf Reveal the Presence of Important Metabolites and Key Pathways Controlling Their Biosynthesis - Yuan, Fang; Yin, Xiu; Zhao, Kaihui; Lan, Xiaozhong (Frontiers in Genetics, 2022)
Codonopsis convolvulacea Kurz. var. vinciflora (Kom.) L.T. Shen is a member of Campanulaceae, which is used in Traditional Chinese Medicine. However, apart from a few Codonopsis species, no detailed knowledge is available on the metabolite composition and respective transcriptome signatures. We report a combined transcriptome and metabolome analysis of the tuber, stem, and leaf of C. convolvulacea and found 1,144 metabolites and 231,840 unigenes in the three experimental groups. The analysis revealed considerable variations in the three tissues. Tubers were rich in amino acids and derivatives, flavonoids, and organic acids, whereas the stems and leaves were rich in alkaloids and flavonoids, respectively. The transcriptome sequencing revealed candidate genes involved in flavonoid, tryptophan, and alkaloids biosynthesis. Particularly, we indicated that the variation in the isoflavone content is linked to the expression of CHI, CYP73A, C3’H, F3H, CYP75B1, ANS, and FLS. Similarly, the levels of indole, L-tyrosine, and tryptamine were also consistent with the expressions of TDC/DDCs in respective tissues. In addition, the expression levels of ASP5, ARO8, GOT, and AOC3 indicated that L-tryptophan is being converted to downstream metabolites. Overall, our datasets present a useful resource for future research on the uses of this medicinal plant and put forward many research questions.